Changes in essential oil content and composition of Tansy (Tanacetum vulgare L.) under foliar application of salicylic and orthophosphoric acids. Issue 1 (2nd January 2016) - Goudarzi, Tahereh; Saharkhiz, Mohammad Jamal; Rowshan, Vahid; Taban, Azin
Abstract: The essential oil (EO) content and composition of Tansy ( Tanacetum vulgare L.) were studied under foliar application of salicylic acid (SA) and orthophosphoric acid (P). Gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) were employed to determine the chemical composition of EOs from the plant. Different concentrations of SA (0, 150, 300, and 450 ppm) and P (0, 0.1, 0.15, and 0.2%) were applied to the plant at different stages of growth including vegetative, floral budding, and full flowering. Based on the results, SA, P and SA × P significantly ( p ≤ 0.05) affected the EO content and chemical composition of the plant. The EO contents (w/w %) ranged from 0.65% to 1%. The total of 29–37 components were identified in the EO samples. The major EO compounds under different SA, P, and SA × P treatments were camphene (0.6–6.2%), sabinene (0.4–6.1%), camphor (4.2–30.4%), trans -thujone (2.4–54%), trans -chrysanthenyl acetate (0.8–52.1%) and germacrene D (2.9–5.7%).